Quantification of Usaramine and its N-Oxide Metabolite in Rat Plasma Using Liquid Chromatography-Tandem Mass Spectrometry. Issue 5 (4th June 2021) - Lin, Feifei; Ma, Yan; Pan, Anni; Ye, Yang; Liu, Jia
Abstract: A sensitive, fast and robust liquid chromatography–tandem mass spectrometry (LC–MS-MS) method was developed and validated for the determination of usaramine (URM) and usaramine N-oxide (UNO) in rat plasma. The separation was conducted on an ACQUITY UPLC BEH C18 Column (50 × 2.1 mm, 1.7 μm) and gradient eluted with mobile phase A (0.1% formic acid with 5 mM ammonium acetate in water) and B (0.1% formic acid in acetonitrile/methanol, 9/1, v/v). The method was linear over the range of 1–2, 000 ng/mL for both analytes. The validated method was applied to investigate the pharmacokinetic behaviors and sex differences of URM and its N-oxide metabolite in rats. After intravenous administration of URM at 1 mg/kg, the AUC0-t values for URM and UNO were 363 ± 65 and 172 ± 32 ng/mL*h in male rats, while 744 ± 122 and 30.7 ± 7.4 ng/mL*h in females, respectively. The clearance of URM was significantly higher in male rats than in females (2.77 ± 0.50 vs 1.35 ± 0.19 L/h/kg, P < 0.05). After oral administration of URM at 10 mg/kg, the AUC0-t values of URM and UNO were 1, 960 ± 208 and 1, 637 ± 246 ng/mL*h in male rats, while 6, 073 ± 488 and 300 ± 62 ng/mL*h in females, respectively. The oral bioavailability of URM in female rats (81.7%) was much higher than in males (54.0%). In conclusion, sex-based differences were observed in the pharmacokinetics, N-oxide metabolism and oral bioavailability of URM.